Electrophysiological, functional and histopathological assessments of high dose melatonin on regeneration after blunt sciatic nerve injury. (February 2020) - Yazar, Uğur; Çakır, Ertuğrul; Boz, Cavit; Çobanoğlu, Ümit; Baykal, Süleyman
Highlights: A single high-dose injection of melatonin preserved myelin sheath after SCI. Melatonin administration prevented axonal loss and accelerated functional recovery. Melatonin helped motor recovery after blunt sciatic nerve injury in rats. Abstract: The aim of this study was to determine the curative effects of high-dose (100 mg/kg) melatonin on peripheral nerve injury. Forty male Wistar albino rats were randomized into four groups as sham, vehicle, melatonin, and ischemia and their right sciatic nerves were exposed. The process was terminated in the sham group. In the other groups, nerve injury was induced by clip compression. The vehicle group was intraperitoneally administered ethanol 0.1 cc (melatonin solvent), while the melatonin group was intraperitoneally administered a single dose of melatonin (100 mg/kg). Following the surgery, sciatic nerve functional index (SFI) was measured using walking track analysis on days 7, 14, and 21, and latency, amplitude, and muscle action potentials (MAP) field values were measured using electroneuromyography (ENMG) on day 21. Histopathologically, edema, axonal degeneration, myelin damage, and inflammatory response were evaluated in all groups. SFI values were noted to be statistically significantly different among the vehicle, melatonin, and ischemia groups, and the melatonin group showed a faster recovery. In the ENMG evaluations, higher amplitude and field values in the melatonin group indicated that melatonin accelerated peripheral nerve recovery. Histopathologically, although fibers with loss of myelin were identified in the melatonin group, the myelin sheath was preserved in general and the axonal structure was noted to be normal. A single injection of high-dose melatonin was found to preserve myelin sheath, prevent axonal loss, and accelerate functional recovery during the nerve regeneration in peripheral nerve injury.